New species of the tribe Meconematini (Orthoptera: Tettigoniidae: Meconematinae: Meconematini) from Sichuan, China - Wang, Hai-Jian; Li, Bo-Liang; Shi, Fu-Ming (Zootaxa, 2019)
Two new species of the subfamily Meconematinae are described, i.e. Neocyrtopsis (Neocyrtopsis) shimianensis Wang & Shi, sp. nov. and Doicholobosa acuta Wang & Shi, sp. nov. from Sichuan, China. All examined specimens are deposited in the Museum of Hebei University.